Killed Whole-Cell Oral Cholera Vaccine Induces CCL20 Secretion by Human Intestinal Epithelial Cells in the Presence of the Short-Chain Fatty Acid, Butyrate - Sim, Ju-Ri; Kang, Seok-Seong; Lee, Daesang; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Immunology, 2018)
Short chain fatty acids (SCFAs) such as acetate, butyrate, and propionate modulate immune responses in the gut. However, the effect of SCFAs on mucosal vaccine-induced immune cell migration is poorly understood. Here, we investigated whether SCFAs modulate chemokine expression induced by the killed whole-cell oral cholera vaccine, Shanchol™, in human intestinal epithelial cells. Shanchol™ induced expression of CCL2, CCL5, CCL20, and CXCL10 at the mRNA level, but not at the protein level. Interestingly, CCL20 secretion was substantially increased by co-stimulation with Shanchol™ and butyrate, while neither acetate nor propionate showed such effect. Enhanced CCL20 secretion was associated with GPR109A activation, and histone deacetylase (HDAC) inhibition. In addition, co-treatment with Shanchol™ and butyrate synergistically increased the secretion of adenosine triphosphate (ATP). Moreover, CCL20 secretion was decreased by inhibiting the extracellular ATP receptor P2X7. However, neither inflammasomes nor caspases were involved in CCL20 production. The culture supernatant of cells treated with Shanchol™ and butyrate augmented human immature dendritic cell migration. Collectively, these results suggest that butyrate enhances Shanchol™-induced CCL20 production in human intestinal epithelial cells via HDAC inhibition and ATP-P2X7 signaling by activating GPR109A. These effects potentially enhance the mucosal immune responses in the gut induced by this oral cholera vaccine.